Interpol's forensic science review - Interpol Forensic Science Symposium; Daeid, Niamh Nic , 1967-; Houck, Max M. (Boca Raton, Florida : CRC Pres, 2010)
Every three years, worldwide forensics experts gather at the Interpol Forensic Science Symposium to exchange ideas and discuss scientific advances in the field of forensic science and criminal justice. This book provides a comprehensive literature review of each of the subject areas
1. Chemical criminalistics -- 2. Drugs and toxicology -- 3. Electronic evidence -- 4. Fire, explosives, and hazardous materials -- 5. Individual evidence
Collection of papers presented at the Interpol Forensic Science Symposium
Includes bibliographical references and index
Keywords: Forensic sciences -- Congresses